Heat Transfer Analysis of Sandwich Plate System Application As Insulation Material for Fishing Vessels Hatches by Finite Element Method - Syauqi, Syafiq Ahmad; Nugroho, Nur Yanu; Hardianto, Didik; Azhar, Ali (Universitas Muhammadiyah Jakarta, 2024)
Fish is a highly perishable food due to its suitability as a substrate for the growth of spoilage microbes, particularly bacteria. One method to maintain fish quality and extend its shelf life is preservation through a cooling system, where the duration of effective storage in the hatch is influenced by the quality of the insulation wall. Previous research modified the hatch insulation wall using a rice husk and white cement composition; however, these materials proved neither effective nor efficient in maintaining cooling temperatures. This study aims to determine the effect of heat transfer in a sandwich plate system on cooling time and temperature. Experiments were conducted using three variations in core layer thickness within a stainless steel-polyurethane-stainless steel configuration. The results indicated that at a temperature of 4°C, the maximum cooling times for each core layer thickness variation were as follows: variation 1 (3-20-3mm) lasted 62.5 hours, variation 2 (3-25-3mm) lasted 64 hours, and variation 3 (3-30-3mm) lasted 65.5 hours. The findings demonstrate that an increase in core layer thickness results in a prolonged maintenance of the cooling temperature within the hatch.